Bilateral Relations Through Conflict And Cooperation: German’s Dilemma Over Russia - Stivani Ismawira Sinambela (Universitas Potensi Utama, 2022)
Since the outbreak of the Ukraine crisis and the implementation of the EU sanctions regime against Russia, Germany took up a leading role in the coordination of the EU’s Russia policy. This policy shift appeared to be a drastic departure from the traditional German Ostpolitik paradigm. Central to this analysis is the concept of geo-economics, which can be broadly defined as the “geostrategic use of economic power”. This article aims to examine how geo-economics influences Germany’s leadership of the EU’s Russia policy, with a particular focus on the study of German domestic politics and the role of relevant economic actors. On the one hand, Germany needs reliable and cost-effective energy to support its world-class industrial economy from Russia. On the other hand, German and Europe security was at stake. This framework is to understand how German policymakers are doing the work of interpreting their national interest and defining appropriate action in response to the dilemma.